Analisis Pemisahan Aset Perusahaan dan Pribadi Melalui Pembentukan Akun Prive untuk Keperluan Pribadi Pemilik pada Online Shop - Leba, Desinta; Ainun, Dara Shafa; Rahayuningsih, Sri (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the application of private accounts as a means of separating corporate and personal assets in online shop (olshop) businesses. The main problem faced by olshop owners is the mixing (commingling) between personal and business funds, which causes inaccurate financial statements and weakens internal control. Based on the business entity concept, as explained by WallStreetMojo and Investopedia, every business must be treated as a separate entity from its owner, so personal transactions must be separated from business transactions. The research method uses an analytical descriptive approach by observing the bookkeeping practices and recording transactions of olshop owners. Data is obtained through interviews and simple financial statement documentation. The results of the study show that the formation of a private account has a positive effect on the regularity of bookkeeping and the quality of financial statements. The withdrawal of personal funds recorded in a private account does not affect the operating profit, but rather reduces the owner's equity, in accordance with the basic accounting principles described by AccountingCoach (2024). Facts in the field show that olshop owners who have not implemented a private account tend to mix personal and business expenses, causing errors in profit recording and difficulties in evaluating financial performance. On the other hand, businesses that consistently implement private accounts have financial statements that are more transparent, easy to audit, and can be trusted by external parties such as banks and investors. This is in line with AccountingInsights' view that recording owner's drawings separately can improve the accountability of small businesses. However, the results of the analysis also show that the establishment of a private account does not necessarily provide legal protection for the owner's personal assets. Based on the entity theory, legal protection can only be achieved if the business turns into a legal entity such as a Limited Liability Company (PT). Thus, the prive account plays an important role in the administrative separation between business and personal finance, but does not guarantee a juridical separation.